Monitoreo de la avifauna silvestre en la parroquia Belisario Quevedo, cantón Latacunga, provincia de Cotopaxi, en el periodo 2013-2014 - Riera Mosquera, Karina Alexandra (2015)
A research study on monitoring of birdlife was carried out in ‘Belisario Quevedo’ Parish. According to current research, the wild birdlife is a good sample of the biological wealth and environmental condition as well as the condition of the place. The areas where the wild birdlife is developed are scarce. Consequently, this problem is the cause of the deforestation. It has destroyed some natural areas in the last years because the people who live in that place need to work in agriculture. Therefore, they need enough areas to work and because of it the forest and natural areas are destroyed. The environment impact is the habitat loss and hence its biodiversity. The interaction is lost with other species of flora and fauna. In addition, those areas provide birds’ food and shelter. A group of wild birds were monitored in four specific sectors: Chavezpamba, Miravalle, San Francisco and Camino al Putzalahua by using the transect method and fixed points.